Serum levels of creatine phosphokinase - Griffiths, P. D. (1964)
Increasing interest in serum enzyme levels in various conditions has led to recognition of the value of the estimation of creatine phosphokinase activity in muscular disorders. Interpretation of the results obtained has been hampered by the lack of adequate information about the `normal range'. Data for the normal levels of creatine phosphokinase in cord blood, children, and adults are presented.